The Cost of Endangered Species Protection: Evidence from Auctions for Natural Resources - Branko Boskovic; Linda Nøstbakken (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper examines the effect that endangered species regulation has on natural resource development. Specifically, we use data from competitive auctions to estimate the effect that land-use regulation protecting endangered caribou in the Canadian province of Alberta has on the price producers pay for the right to extract oil. We exploit a regression discontinuity design to evaluate how prices differ along regulation boundaries that constrain resource development. The auction format and the regulation discontinuity allow use to measure the total cost of the regulation. We find that producers pay 24% less on average for oil leases that are regulated and that the total net present value cost of the regulation exceeds 1.15 billion for leases sold between 2003-2012, all of which is borne by the government. In spite of these costs, the populations of endangered caribou remain in widespread decline.
Keywords: Q58; D44; Q52; L71; 330; endangered species regulation; auctions; natural resources; oil